Extrinsic motivation in Sekolah Menengah Kebangsaan Dato' Sri Amar Di Raja, Muar / Noor Alina Halil - Halil, Noor Alina (Faculty of Education, 2014)
Motivation can be defined as the psychological state that leads an individual to behave in a certain manner, which drives one to behave like that or makes one enthusiastic about performing a task. Unmotivated students would not expend the necessary effort to learn, while motivated student will. Malaysian students are generally said to be more extrinsically motivated rather than intrinsically motivated. This study is aimed to determine the level of extrinsic motivation of school students. The six extrinsic variables are competition dimension, affiliation dimension, social power dimension, praise dimension token-reward dimension, and marks dimension. This study involves 100 students from mixture of different age, class and gender. The sets of questionnaire distributed intended to identify whether these six variables influence the students’ motivation in learning and which of extrinsic motivators is the most significant one for the students. The results showed that all the variables averagely influence the students’ motivation and the variable that influences them the most is the mark dimension.